Dynamic Governance in Bureaucratic Reform: A Case Study of Dispendukcapil Surabaya - Qonita, Firzan (CV. Era Digital Nusantara, 2024)
Abstract: Bureaucratic reform aims to improve and enhance the quality of public services. One approach to achieving this is by adopting a dynamic approach to governance. This approach focuses on dynamic governance. One example of bureaucratic reform in administrative services in Indonesia is in East Java, specifically in Surabaya. In Surabaya, the Dispendukcapil handles administrative population registration. The Surabaya city government needs to adopt the dynamic governance concept as a governance framework. This concept enables the government and its policies to adapt to uncertain situations and the various changes that occur, with the goal of ensuring that government policies remain relevant, effective, and efficient for long-term objectives. However, the current challenge lies in the increasingly advanced technology, while the population in Surabaya remains diverse, making it a challenge for Dispendukcapil Surabaya to improve services that can be accessed by all segments of Surabaya’s population. Purpose: The purpose of this study is to analyze the Bureaucratic Reform in Dispendukcapil Surabaya. Design/Methodology/Approach: This research employs a descriptive qualitative approach. The focus of this study is based on the theory of Dynamic Governance. The data sources for this research consist of primary and secondary data. Data collection techniques include interviews, observations, and documentation. The data analysis techniques involve data collection, data reduction, data presentation, and data verification. Findings: In this case, the bureaucratic reform in the Dispendukcapil based on the Dynamic Governance approach has seen some progress. In the context of